Peningkatan Aktivitas dan Hasil Belajar Siswa dengan Model Flipped Classroom Pada Pembelajaran Jarak Jauh - Erna Sari Agusta (Direktorat GTK Madrasah Ditjen Pendis Kementerian Agama Republik Indonesia, 2022)
Like virtual classrooms, distance learning programs are a space for interaction between students and teachers to be able to give and receive information that can increase their knowledge. However, the facts that occur in the field show that the distance learning system has an impact on the lack of student learning activities. This lack of learning activities also has an impact on the low acquisition of learning outcomes. This study aims to improve student activities and learning outcomes with the flipped classroom model in distance learning. This type of research is Classroom Action Research with the Kemmis McTaggart Model. The study was conducted on students of class VII-2 at MTsN 28 Jakarta with a total of 32 people. The time of the study was carried out from February to March 2021. The results showed that the flipped classroom model encouraged students to carry out learning activities and be involved in distance learning. This is indicated by an increase in the number of students who explain by 6.5%, answer questions by 29.1%, and provide responses by 21.4%. The increase in learning activities also has an impact on the acquisition of the average value of learning outcomes which continues to increase starting from 68.97 in the first cycle, 73.05 in the second cycle, and 77.18 in the third cycle. Thus, it can be concluded that the application of the flipped classroom model in distance learning can improve student activities and learning outcomes.